2013
DOI: 10.1063/1.4807172
|View full text |Cite
|
Sign up to set email alerts
|

Laser triggered Z-pinch broadband extreme ultraviolet source for metrology

Abstract: We compare the extreme ultraviolet emission characteristics of tin and galinstan (atomic %: Ga: 78.35, In: 14.93, Sn: 6.72) between 10 nm and 18 nm in a laser-triggered discharge between liquid metal-coated electrodes. Over this wavelength range, the energy conversion efficiency for galinstan is approximately half that of tin, but the spectrum is less strongly peaked in the 13–15 nm region. The extreme ultraviolet source dimensions were 110 ± 25 μm diameter and 500 ± 125 μm length. The flatter spectrum, and −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…8,9 There is extensive literature on Z-pinch discharges in LPP for X-ray 10 or extreme ultraviolet radiation sources. 11,12 Here, we report on the inductive heating and magnetic focusing of a LPP during the first few microseconds of ablation plume expansion. Time-resolved imaging was used to capture the expansion dynamics, with and without the pulsed magnetic field.…”
mentioning
confidence: 99%
“…8,9 There is extensive literature on Z-pinch discharges in LPP for X-ray 10 or extreme ultraviolet radiation sources. 11,12 Here, we report on the inductive heating and magnetic focusing of a LPP during the first few microseconds of ablation plume expansion. Time-resolved imaging was used to capture the expansion dynamics, with and without the pulsed magnetic field.…”
mentioning
confidence: 99%
“…Atoms 2020, 8, x FOR PEER REVIEW 2 of 25 obtained a relatively flatter spectrum with respect to a pure Sn plasma and an emission structure that reflected the presence of its composite elements [7].…”
Section: Methodsmentioning
confidence: 99%
“…It is found that higher laser energy, higher voltage, and shorter gap distance conduce to the reduction of the delay. Discharge current I(t) is described by a simple underdamped RLC circuit [14] as expressed in Eq. ( 1), the plasma produced between electrodes is represented equivalently by a resistance R and an inductance L,…”
Section: Discharge Characteristicsmentioning
confidence: 99%
“…[6] To meet these demands, the EUV light sources produced respectively from three kinds of plasma discharges have been proposed in recent years: Xe gas discharge produced plasma (Xe-GDPP), [7] Sn laser-produced plasma (Sn-LPP), [8] and Sn laser-assisted discharge plasma (Sn-LDP). [9] In 2006, Jonkers compared EUV output power emitted from the LPP, Z-pinch plasma, and vacuum arc plasma in a tin vapour. [10] In 2011, Banine et al compared the EUVemitting plasma characteristics such as spectra, formation of the plasma, and associated debris production in LDP source and LPP source.…”
Section: Introductionmentioning
confidence: 99%